Penjernihan Minyak Jelantah dengan Menggunakan Terong (Solanum melongena) - Rizki, Suci Yulia; Hardeli, Hardeli; Ningsih, Sherly Kasuma Warda; Pernadi, Niza Lian; Sidiq, Aqil Marsya; Nizar, Umar Kalmar (Departemen Kimia FMIPA UNP, 2024)
Used cooking oil is used oil that has been heated repeatedly with high heat. At high heating, the triglycerides contained in used cooking oil can be hydrolyzed into free fatty acids. In addition, it can form free radical compounds that can cause serious diseases such as cancer. Therefore, this study aims to clarify used cooking oil using eggplant (Solanum melongena). Eggplant is rich in beneficial ingredients such as high levels of flavonoids, phenolics and antioxidants. Eggplant can be used as an adsorbent that can clarify used cooking oil. This study used the method of heating used cooking oil at a temperature of 160⁰C and the mass variations of the eggplant were 5, 10 and 15 grams. The result of this study is that the use of 10 grams of eggplant is proven to clear used cooking oil. which was previously blackish brown underwent degradation of light brown color accompanied by a decrease in the density value to 0.94 g/mL, the acid number to 2.08 mg/KOH, and an increase in the flow rate value to 0.2987 ml/s, a saponification number of 80.17 mg KOH in used cooking oil.